INTELLIGENT DECISION SUPPORT SYSTEMS FOR SEARCHING THE OPTIMUM PALM OIL BASED BIO-ENERGY SUPPLY CHAIN BY USING ANT COLONY OPTIMIZATION METHOD - Ditdit N. Utama, Taufik Djatna, Erliza Hambali, Marimin dan Dadan Kusdiana (Jurnal Teknologi Industri Pertanian, 2011)
ABSTRACT  Main backgrounds of developing model of intelligent decision support  systems, for searching the most optimum supply path in palm oil based bio-energy supply chain management, are importance of supply chain management concept implementation in doing business activities that involve more than one companies; importance of palm oil based bio-energy management availability; and difficulty of management and searching of the most optimum path of perishable product supply chain. The objectives of this paper were the explanation of setting optimum value and searching the most optimum path of palm oil based bio-energy supply chain. The method used in this paper was combination of Balance Score Card (BSC), Supply Chain Operation Reference (SCOR), and ant colony optimization (SCO) methods. On the other hand, this paper explained the model suggestion of the most optimum path and comparation of developed model with the common model (shortest path). In conclusion, the developed model gave more  optimum result than shortest path mehod gave. Furthermore, the model could show the optimum value that was generated from supply chain perspectives. It was better than shortest path method. Whereas, the shortest path method showed only the shortest path that involved only one variable, distance. Finally, the paper suggested that combination of the fuzzy and ant colony optimization method research was needed to do.   Keywords: palm oil based bio-energy, intelligent decision support system, optimum path, supply chain management, ant colony optimization  ABSTRAK